MARKET TRENDS: ADAPTATION OF MSMEs SUMBER PANGAN JAYA SOLO IN THE DIGITALIZATION ERA - Yunardhani, Rakei; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (Nusantara Economics and Entrepreneurships Journals, 2024)
The development of information and communication technology has changed the global business landscape, including in Indonesia. Micro, Small, and Medium Enterprises (MSMEs) are one of the sectors most affected by the e-commerce trend. This article aims to explore how MSMEs in Indonesia, especially in the culinary and craft sectors, adapt to the demands of the digital market. The research method used is a quantitative survey method. The object of this study is MSMEs Sumber Pangan Jaya Solo which is engaged in the retail sector and has been established since 2021. This study uses SEM-PLS analysis with SMARTPLS4 software. The data used is primary data from the results of the questionnaire with a sample size of 100 from the calculation results using the Slovin formula. The results of the study show that Digital Marketing Strategy has an effect on Marketing Performance, Digital Training has an effect on Digital Marketing Strategy, Digital Training has an effect on Marketing Performance, Technology has an effect on Digital Marketing Strategy, and Technology has no effect on Marketing Performance